The Influence of the Procurement System and Vendor Reputation on the Success of Construction Projects in the Construction of the Jakarta RDF Plant with the E-Procurement System as a Moderator - Robert Edward; Sania Zahroh (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study uses e-procurement as a moderator to investigate how the procurement system and vendor reputation affect construction projects' success in the building of the RDF Plant Jakarta. The study's participants were KSO Wika-Jaya Konstruksi personnel. In this study, a quantitative descriptive approach was used. The analysis method used in this study is structural equation modeling. To look at the direct and moderating effects between variables, the research design uses causality. SmartPLS (Partial Least Square) 3.0 is the program in use. Purposive sampling is the method employed, specifically using a non probability sampling technique called purposeful sampling, researchers specifically choose participants based on predetermined standards or traits that align with the study's goals. The sample size is 100 respondents. Data collecting methods distribute questionnaires via Google Form in order to obtain primary information. The results of the study indicate that the procurement system significantly and favorably influences the success of construction projects, a vendor's good reputation has a big positive effect on the success of construction projects, and that e-procurement significantly and favorably strengthens the link between the procurement system and construction project success.